Encyclopedia of Life Sciences 2010
DOI: 10.1002/9780470015902.a0000747.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Closteroviridae

Abstract: Closteroviridae is a family of plant viruses with filamentous, helically constructed particles showing distinct cross‐banding and varying in length from 650 nm (species with fragmented genome) to over 2000 nm (species with monopartite genome). The genome is a single‐stranded, positive‐sense RNA ( ribonucleic acid ), with size varying from 13 000 to nearly 19 000 nucleotides, thus being among the largest known for plant viruses. The family comprises three genera, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The graft transmissible agent responsible (‘Little cherry pathogen’) was previously considered to be a single virus species but studies have shown that two viruses belonging to the Closteroviridae family, Little cherry virus 1 (LChV1, Jelkmann, ) and Little cherry virus 2 (LChV2, Eastwell and Bernardy, ; Rott and Jelkmann, , ) are associated with the disease. LChV1 is a member of the Velarivirus genus, while LChV2 belongs to the Ampelovirus genus (Martelli et al., ,b; Martelli and Candresse, ). For the sake of simplicity, when collectively referred to, LChV1 and LChV2 will be designated in what follows as Little cherry viruses or LChV.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…The graft transmissible agent responsible (‘Little cherry pathogen’) was previously considered to be a single virus species but studies have shown that two viruses belonging to the Closteroviridae family, Little cherry virus 1 (LChV1, Jelkmann, ) and Little cherry virus 2 (LChV2, Eastwell and Bernardy, ; Rott and Jelkmann, , ) are associated with the disease. LChV1 is a member of the Velarivirus genus, while LChV2 belongs to the Ampelovirus genus (Martelli et al., ,b; Martelli and Candresse, ). For the sake of simplicity, when collectively referred to, LChV1 and LChV2 will be designated in what follows as Little cherry viruses or LChV.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…GLRD is caused by several related positive single-stranded RNA virus species in the family Closteroviridae , which contains the largest known plant RNA virus genomes [4]. All GLRD-causing viruses are phloem-limited [5] and infect Vitis hosts [6]. The mealybug-transmitted viruses are in the genus Ampelovirus , and Grapevine leafroll-associated virus 2 , which has no known vector, is in the genus Closterovirus [6].…”
Section: Introductionmentioning
confidence: 99%